PERANCANGAN KNOWLEDGE MANAGEMENT UNTUK DETEKSI DINI PENYIMPANGAN PERKEMBANGAN ANAK MENGGUNAKAN KUESIONER PRA SKRINING PERKEMBANGAN (KPSP) BERBASIS ONTOLOGI - , KALIKAUTSAR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The quality of child development as a potential next generation need routine screening for easier further handling or intervention. One of child developmental disorders screening methods suggested by the Ministry of Health is KPSP. However, KPSP carried out in health centers, while the optimal early detection is done at home as a natural environment for the child. On the other hand, the mother's ability to perform screening, stimulations, and interventions also need to be improved. This research aims to develop a knowledge management for early detection of developmental disorders with KPSP as a technology solution that can be applied for early detection at home by mother. With the ontology system, knowledge management is developed to facilitate the use of KPSP than conventional methods, expected for mother to learn and perform a routine early detection of child development. The result of this study is a model of early detection of developmental disorders ontology using KPSP implemented in ProtÃ©gÃ© 4.3. The system was designed to use 5 classes, those were age for KPSP age groups with 16 instances, baby for child who use KPSP with 3 instances, kpsp for KPSP questions with 158 instances, status for KPSP answerâs interpretation results with 3 instances, and stimulation for stimulation points that should be given to children who use KPSP with 228 instances. The system was equipped with 35 rules to generate relationships between classes and tested according to KPSP flow using SPARQL. The ontology models not only help in the screening process with KPSP but also provide intervention and stimulation decisions for child better development. Keywords : knowledge management, ontology, KPSP, intervention, stimulation